Sterol-based oleogels characterization envisioning food applications - Martins, Artur J. (2019)
BACKGROUND Phytosterols, in particular a mixture of pure oryzanol and sitosterol, develop a tubular system that is able to structure oil. In this study, different concentrations of a combination of oryzanol and a commercial phytosterol mixture, Vitaesterol®, were used for the development of edible oil oleogels. RESULTS Small Angle Xray Scattering (SAXS) and XRay Diffraction (XRD) were used to characterize at nano and molecular scale the aforementioned oleogels and confirm the formation of sterolsbased hollow tubule structures. Increased hardness was observed with the increase of gelator content used in oleogel manufacturing. The produced oleogels showed promising features such as tailored mechanical strength and low opacity, which are important features when considering their incorporation into food products. CONCLUSION Despite of differences in gel strength, oleogels exhibited textural characteristics that make these structures suitable for incorporation in food products. The oil migration profile associated to these oleogels can provide a solution for the controlled release of lipophilic compounds as well as for the retention of oil in cooked food products.